Establishment of Photoaging In Vitro by Repetitive UVA Irradiation: Induction of Characteristic Markers of Senescence and its Prevention by PAPLAL with Potent Catalase Activity1. (7th March 2018) - Yoshimoto, Satoshi; Yoshida, Moemi; Ando, Hideya; Ichihashi, Masamitsu
Abstract: To understand a role of UVA radiation in photoaging of the skin, we established a model of photoaging cells using cultured human dermal fibroblasts. Repeated low‐dose UVA radiation for 10 consecutive days induced senescence in fibroblasts, characterized with (1) increased level of senescence‐associated β ‐galactosidase, (2) flattened large cell shape, (3) accumulation of reactive oxygen species, (4) yellowish coloration and (5) expression of p16. These were also observed in chronologically aged fibroblasts (doubling times >20), whereas none of these were detected in young cells (doubling times <10). Collectively, we propose that fibroblasts exposed to repetitive UVA radiation may be a good model of aged cells to study the mechanism of aging and photoaging and further to search for novel agents preventing cellular senescence. In addition, H2 O2 was produced in the culture medium by a single low dose of UVA irradiation. Further, PAPLAL, a nanoparticle of platinum and palladium having potent catalase‐like activity, significantly delayed the onset of H2 O2 ‐induced cell senescence. The present study strongly indicates that repetitive short‐term UVA irradiation induces aging of cells possibly via H2 O2 and may be suppressed by potent anti‐H2 O2 agents. Abstract : This study established a method to induce photoaged cells in vitro by repetitive UVA irradiations and demonstrated a role of H2 O2 in UVA radiation–induced cellular senescence. We discuss the importance of daily use of anti‐ROS agents based on our current study of PAPLAL for the prevention of photoaging and hope our investigation contributes to the maintenance of young skin till aged.